Interleukin-18 in Inflammatory Kidney Disease - Hirooka, Yasuaki; Nozaki, Yuji (Frontiers in Medicine, 2021)
Interleukin (IL)-18, a member of the IL-1 superfamily, is a proinflammatory cytokine that is structurally similar to IL-1β. IL-18 promotes the production of interferon gamma (IFN-γ) and strongly induces a Th1 response. IL-18 drives the same myeloid differentiation factor 88 (MyD88)/nuclear factor kappa B (NF-κB) signaling pathway as IL-1β. In physiological conditions, IL-18 is regulated by the endogenous inhibitor IL-18 binding protein (IL-18BP), and the activity of IL-18 is balanced. It is reported that in several inflammatory diseases, the IL-18 activity is unbalanced, and IL-18 neutralization by IL-18BP is insufficient. IL-18 acts synergistically with IL-12 to induce the production of IFN-γ as a Th1 cytokine, and IL-18 acts alone to induce the production of Th2 cytokines such as IL-4 and IL-13. In addition, IL-18 alone enhances natural killer (NK) cell activity and FAS ligand expression. The biological and pathological roles of IL-18 have been studied in many diseases. Here we review the knowledge regarding IL-18 signaling and the role of IL-18 in inflammatory kidney diseases.